A conceptual framework for the analysis of determinants of m-commerce acceptance - Rind, Muhammad Malook; Koondhar, Muhammad Yaqoob; Chandio, Fida Hussain; Shah, Asadullah (2015)
With the emergence of internet and World Wide Web, traditional businesses got a new opportunity to compete globally. Traditional bricks-and-mortar businesses became electronic business (e-business) with the help of Information and Communication Technology (ICT) tools. Smart phone technology brought a new revolution in e-business market. A new term of Mobile Commerce (M-Commerce) emerged and set a new trend in commerce and business. M-commerce usage trend in developing economies still seems to take very slow steps as compared to developed countries like USA, UK, Australia and others. The purpose of this study is to extend research on the acceptance of M-Commerce in context of developing economies. A conceptual framework of some widely used technology adoption and social psychology theories including, Technology Acceptance Model (TAM), Innovation Diffusion Theory (IDT), Unified Theory of Acceptance and Use of Technology (UTAUT), is proposed to diagnose the significant factors of MCommerce acceptance in developing economies.